2023
DOI: 10.1051/0004-6361/202346778
|View full text |Cite
|
Sign up to set email alerts
|

The RoboPol sample of optical polarimetric standards

D. Blinov,
S. Maharana,
F. Bouzelou
et al.

Abstract: Context. Optical polarimeters are typically calibrated using measurements of stars with known and stable polarization parameters. However, there is a lack of such stars available across the sky. Many of the currently available standards are not suitable for medium and large telescopes due to their high brightness. Moreover, as we find, some of the polarimetric standards used are in fact variable or have polarization parameters that differ from their cataloged values. Aims. Our goal is to establish a sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In the K band, Wilking et al (1980) found p(K ) = 0.0133 ± 0.0005, and Bailey & Hough (1982) found p(K ) = 0.0113 ± 0.0003. Blinov et al (2023) report substantial variations of U/I and Q/I over 2400 days of observations.…”
Section: » mentioning
confidence: 91%
“…In the K band, Wilking et al (1980) found p(K ) = 0.0133 ± 0.0005, and Bailey & Hough (1982) found p(K ) = 0.0113 ± 0.0003. Blinov et al (2023) report substantial variations of U/I and Q/I over 2400 days of observations.…”
Section: » mentioning
confidence: 91%
“…The observations were conducted in Sloan Digital Sky Survey (SDSS)-r ′ and Johnsons-Cousins R bands. Observations of both bands were considered together, as we verified with standard stars measurements that these filters are essentially equivalent (Blinov et al 2023). The selection of these filters was also informed by the fact that the upcoming PASIPHAE survey will be operating in SDSS-r ′ .…”
Section: Data Aquisition and Reduction: Northmentioning
confidence: 99%
“…The data reduction and calibration were performed with the standard RoboPol pipeline, as outlined in King et al (2014); Panopoulou et al (2015); Blinov et al (2021). Uncertainties of the systematic error are on the order of ∼0.1% in the mask of the instrument (Blinov et al 2023). We note that these uncertainties concern measurements of individual targets.…”
Section: Data Aquisition and Reduction: Northmentioning
confidence: 99%
See 1 more Smart Citation